PSVII-14 The Role of Supplemental Beef as a Healthy Alternative to a Sugar Snack during Pregnancy on Fetal Developmental Programming in Swine. (7th December 2018) - Hoyle, A; Nelson, M; Swanson, K; Vonnahme, K; Berg, E; Ward, A
Abstract: The purpose of this study was to use a swine biomedical model to investigate the impact of substituting supplemental beef in place of sugar snack on fetal developmental programming. A total of 21 multiparous sows (Landrace x Yorkshire; d 30 BW 221.58 kg ± 33.26) were bred via AI to a common sire and fed a complete gestation diet (corn-soybean meal, CSM) at one percent of gestational BW through d 110 (±0.58) of gestation. Sows were randomly assigned to 1 of 4 supplement treatments: control supplement, 126 g CSM (CON, n = 5); sugar supplement, 85 g crystalized sugar (SUGAR, n = 5); cooked beef supplement, 110 g (BEEF, n = 6); or sugar + beef supplement, 55 g cooked beef and 43 g crystalized sugar (B+S, n = 5). Supplements were fed three times daily from d 40 to d 110 of gestation. Sows were euthanized on d 111 (±0.58 d) of gestation. The longissimus muscle was collected from one male and one female fetus of median weight from each litter and preserved in RNAlater. Gene expression was measured via qPCR with HPRT1 as the reference gene. The following genes were selected due to associations with metabolic function: GYS-1, HK2, IGF1R, IRS-1, LEPR, INSR, and SREBP-1C. Data were analyzed using the GLM procedure of SAS. No significant effects of treatment were observed for any of the genes analyzed: GYS-1 (P = 0.37); HK2 (P = 0.34); IGF1R (P= 0.74); IRS-1 (P= 0.27); LEPR (P = 0.32); INSR (P = 0.38); SREBP-1C (P = 0.49). There was also no effect of sex or sex by treatment interaction (P > 0.05). We conclude that maternal beef or sugar supplementation during gestation did not alter fetal muscle gene expression in this swine model.